A review of personal care products in the aquatic environment: Environmental concentrations and toxicity - Brausch, John M.; Rand, Gary M. (Chemosphere (Oxford), 2011)
Considerable research has been conducted examining occurrence and effects of human use pharmaceuticals in the aquatic environment; however, relatively little research has been conducted examining personal care products although they are found more often and in higher concentrations than pharmaceuticals. Personal care products are continually released into the aquatic environment and are biologically active and persistent. This article examines the acute and chronic toxicity data available for personal care products and highlights areas of concern. Toxicity and environmental data were synergized to develop a preliminary hazard assessment in which only triclosan and triclocarban presented any hazard. However, numerous PCPs including triclosan, paraben preservatives, and UV filters have evidence suggesting endocrine effects in aquatic organisms and thus need to be investigated and incorporated in definitive risk assessments. Additional data pertaining to environmental concentrations of UV filters and parabens, in vivo toxicity data for parabens, and potential for bioaccumulation of PCPs needs to obtained to develop definitive aquatic risk assessments.